GMAT Club

Kudos owned by the user


Bunuel received 5 Kudos for post Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =.

GiverPostDate
Kimberly77Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =05-Aug-2022
Vivek97Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =02-Mar-2019
sedgwickRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =24-Mar-2018
Gmad2015Re: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =02-Feb-2015
MehrabanRe: If x(2x + 1) = 0 and (x + 1/2)(2x - 3) = 0, then x =08-Feb-2014

Page 1 of 1